2023
DOI: 10.3389/fsurg.2023.1074438
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Curative effect of OA-PICA protected bypass in severe PICA-complicated vertebral artery stenosis treatment: Results in 3 cases

Abstract: ObjectivesWe aimed to explore the results of OA-PICA-protected bypass grafting in patients with severe stenosis of the vertebral artery combined with PICA.MethodsThree patients with vertebral artery stenosis involving the posterior inferior cerebellar artery, treated by the Department of Neurosurgery of Henan Provincial People's Hospital from January 2018 to December 2021, were retrospectively analyzed. All the patients underwent Occipital Artery–Posterior Inferior Cerebellar Artery (OA-PICA) bypass surgery fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Although the number of OA and SV specimens obtained in this study was too small for meaningful comparison, the existing literature indicates that anastomosis in the posterior circulation is technically more challenging than that in the anterior circulation. Conducting further pathological studies with a larger number of cases may be imperative for comprehensive insights [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the number of OA and SV specimens obtained in this study was too small for meaningful comparison, the existing literature indicates that anastomosis in the posterior circulation is technically more challenging than that in the anterior circulation. Conducting further pathological studies with a larger number of cases may be imperative for comprehensive insights [32].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, while bypass patency was confirmed in all moyamoya disease and atherosclerosis cases, the obtained patency results extended up to 1 year. However, there are reports of graft occlusion occurring more than 1 year later [32]. Investigating the relationship between disease, pathology, and long-term patency needs additional studies for a more thorough understanding.…”
Section: Limitationmentioning
confidence: 99%